Early Oral Language Comprehension, Task Orientation, and Foundational Reading Skills as Predictors of Grade 3 Reading Comprehension - Janne Lepola; Julie Lynch; Noona Kiuru; Eero Laakkonen; Pekka Niemi (John Wiley & Sons, Inc., 2022)
The present five-year
longitudinal study from preschool to grade 3 examined
the developmental associations among oral language comprehension,
task orientation, reading precursors, and reading fluency, as well as their
role in predicting grade 3 reading comprehension. Ninety Finnish-speaking
students participated in the study. The students’ oral language comprehension
(vocabulary knowledge, listening comprehension, and inference making)
and task orientation were assessed in preschool, kindergarten, and grade 3.
Reading precursors (letter knowledge and phonological awareness) were assessed
at the first two timepoints and reading fluency at the third timepoint.
Structural equation modeling showed that oral language comprehension,
reading fluency, and task orientation each contributed uniquely to concurrent
reading comprehension, and together they accounted for 76% of variance
in reading comprehension. A reciprocal relationship was found between oral
language comprehension and task orientation from preschool through kindergarten
to grade 3, a finding that extends our knowledge of the longitudinal
determinants of reading comprehension.